Evaluation of nurses’ learning in an online course about venous leg ulcer (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To evaluate the degree of knowledge of nurses about venous leg ulcer (VLU) and compressive therapy (CT); comparing the degree of knowledge on the subject between nurses with and without specialized training in stomatherapy, after the online course; and analyze the demographic and educational variables associated with learning. Methods: A quasi-experimental and comparative study in which a didactic intervention was tested in two different groups of nurses, through the application of a questionnaire to evaluate learning before and after the course. Data were analyzed by McNemar, chi-square, F of ANOVA tests, Student t and generalized estimation equations. Results: The specialist nurses obtained average scores of 7.79 and 9.07 and the generalists of 6.39 and 8.49, respectively, in the pre and post-course. Age equal or higher to 30 years influenced to the highest degree of knowledge after the course. Conclusion: The course allowed learning about the theme in both groups. Specialist nurses had greater knowledge on the subject when compared to generalist nurses.
Keywords: Stomatherapy; Varicose ulcer; Compressive bandages; Computing in nursing; Correspondence course; Learning